2019
DOI: 10.1111/jac.12376
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric ozone pollution reduces the yield of African crops

Abstract: Northern, Southern and Equatorial Africa have been identified as among the regions most at risk from very high ozone concentrations. Whereas we know that many crop cultivars from Europe, north America and Asia are sensitive to ozone, almost nothing is known about the sensitivity of staple food crops in Africa to the pollutant. In this study cultivars of the African staple food crops, Triticum aestivum (wheat), Eleusine coracana (finger millet), Pennisetum glaucum (pearl millet) and Phaseolus vulgaris (bean) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 86 publications
(105 reference statements)
1
18
0
Order By: Relevance
“…The resistant genotype can recover by producing some new leaves from week eight and it reduces the percentage of leaves that are larger than 25% injury. This result is consistent with the studies by [20], which also showed that higher O 3 exposure led to higher occurrence of O 3 injury in P. vulgaris.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The resistant genotype can recover by producing some new leaves from week eight and it reduces the percentage of leaves that are larger than 25% injury. This result is consistent with the studies by [20], which also showed that higher O 3 exposure led to higher occurrence of O 3 injury in P. vulgaris.…”
Section: Discussionsupporting
confidence: 93%
“…The standard deviation and difference significance level are displayed in Tables 1 and 2. For the visible leaf injury data, we followed the statistical methodology performed by Hayes et al (2019) [20], who tested if the proportion of leaves per injury category varied with the genotype of the bean. We used the "multinom" function in the "nnet" package in R [45,46] to perform a multinomial logistic regression models on the relationship between leaf injury and genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research at a range of O 3 concentrations during the whole growing season is needed to develop robust O 3 flux-yield relationship and assess whether mitigation of adverse impacts of O 3 on wheat yield at reduced irrigation can simply be explained by a reduction in the phytotoxic O 3 dose [46]. Developing such a flux–yield relationship for the Kenyan wheat variety Korongo, a very O 3 -sensitive variety [43], would also allow comparison of the O 3 -sensitivity of an African wheat variety to those from other continents. Preferably, further research with Korongo should be conducted under Kenyan growth conditions as Korongo might perform differently under local conditions compared to the environmental conditions at the UK study site.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesised that reduced irrigation will reduce g s and therefore the accumulated uptake of O 3 , resulting in a delay in an O 3 -induced decline in flag leaf photosynthesis and an improved yield compared to full irrigation. An O 3 -sensitive African variety of wheat [43] was exposed to low (daylight mean O 3 concentration of 25 ppb, with peak concentrations aimed at 30 ppb) and high O 3 (daylight mean O 3 concentration of 45 ppb, with peak concentrations aimed at 80 ppb) for five days a week in hemi-spherical glasshouses for four weeks during flowering and grain fill. The high O 3 treatment represents surface peak O 3 concentrations observed in South Africa during periods of biomass burning [10].…”
Section: Introductionmentioning
confidence: 99%